Architectural and Artistic Solution of Museum Exhibition - Shahrizoda, Beknazarova (European Multidisciplinary Journal of Modern Science, 2022)
In this article we will talk about the architectural and artistic solution of museum vision. The author, relying on cultural data and written sources, introduced clarifications to the problem on the basis of existing scientific and historical literature and studied the existing peculiarities of the architectural and artistic solution of museum vision.